2004
DOI: 10.1002/ijc.20765
|View full text |Cite
|
Sign up to set email alerts
|

NBS1 657del5 mutation may contribute only to a limited fraction of breast cancer cases in Russia

Abstract: The gene for Nijmegen chromosomal breakage syndrome (NBS1) plays a role in a variety of processes protecting chromosomal stability. Recently, it was suggested in a Polish case-control study that the founder hypomorphic mutation in NBS1, 657del5, which occurs in approximately 0.5% of Slavic subjects, may be associated with an increased risk of breast cancer (BC). We attempted to validate these findings in Russian subjects, who are also of Slavic descent. Heterozygous carriers for the 657del5 mutation were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 29 publications
1
41
1
1
Order By: Relevance
“…Although a number of published reports have suggested that mutations in NBS1, especially 657del5, is associated with elevated risk for some cancers, including ovarian (13), breast (7,8,10), melanoma (7,9), and lymphoid malignancies (7,11,12), such findings have not been replicated in other studies (21)(22)(23)(24). For prostate cancer, Cybulski et al (5) found that the 657del5 mutation was a risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a number of published reports have suggested that mutations in NBS1, especially 657del5, is associated with elevated risk for some cancers, including ovarian (13), breast (7,8,10), melanoma (7,9), and lymphoid malignancies (7,11,12), such findings have not been replicated in other studies (21)(22)(23)(24). For prostate cancer, Cybulski et al (5) found that the 657del5 mutation was a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The rare variant, R215W, has also been implicated as a pathogenic mutation in Nijmegen breakage syndrome (32). Conservation studies also show that this position is highly conserved and that this change is predicted to be damaging (8,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports of the contribution of mutations in different members of the MRN complex to hereditary breast cancer risk in specific populations, however, have been difficult to confirm elsewhere (8,9). A study of 435 familial breast cancer cases from the United Kingdom also failed to observe Rad50 c.687delT; in this same study, a more extensive sample of Finnish familial cases also observed no additional instances of this mutation (10).…”
Section: Resultsmentioning
confidence: 65%
“…Nonetheless, their findings could be interpreted as an argument against the use of bilateral BC patients, especially those with synchronous form of the disease, in genetic association studies. Among the reports quoted in the Table I, only Buslov et al 21 published carrier frequencies for synchronous versus metachronous bilateral BC (1/44 (2.3%) versus 1/129 (0.78%), respectively). To extend this analysis, we have also retrieved the information from original data sets for the studies of Sokolenko et al 16 and Chekmariova et al 20 The frequency of BRCA1 5382insC mutation was 5/53 (9.4%) in synchronous and 10/91 (11.0%) in metachronous bilateral BC, i.e.…”
mentioning
confidence: 99%